Aerogel based on bisphenol A type diether dianhydride monomer and preparation method thereof

By interspersing nano zirconium phosphate materials into polyimide aerogels and combining the crosslinking network of modified zirconium phosphate and polyimide, the problems of low strength and volatility of polyimide aerogels are solved, and the excellent mechanical properties and flame retardant and thermal insulation properties of the aerogel are achieved.

CN119613805AInactive Publication Date: 2025-03-14YINGKOU XINGFU CHEM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411871721.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

During the preparation process, polyimide aerogel has problems such as low strength, volatility, poor surface quality, severe volume shrinkage and possible cracking, which is difficult to meet the mechanical properties requirements for long-term use.

Method used

Using aerogel preparation method based on bisphenol A type diether dianhydride monomer, the toughness of the aerogel is improved and volume shrinkage is inhibited by interspersing nanozirconium phosphate materials into the polyimide skeleton and combining the crosslinking network of modified zirconium phosphate and polyimide.

Benefits of technology

The excellent mechanical properties of the aerogel are achieved, including high elasticity and recovery, avoiding volume shrinkage and deformation, enhancing flame retardant and thermal insulation performance, and meeting the requirements of long-term use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613805A_ABST
    Figure CN119613805A_ABST
Patent Text Reader

Abstract

The invention provides aerogel based on a bisphenol A type diether dianhydride monomer and a preparation method thereof, and is characterized in that the preparation method comprises the following steps: step 1, synthesizing flame-retardant diamine; 2, carrying out condensation polymerization on the flame-retardant diamine and bisphenol A type diether dianhydride to obtain a polyamide acid prepolymer; step 3, mixing the polyamide acid prepolymer with the modified zirconium phosphate, and carrying out sol-gelation and freeze-drying, so as to obtain polyamide acid-zirconium phosphate composite aerogel; and 4, carrying out thermal imidization treatment to obtain the polyimide-zirconium phosphate composite aerogel. The aerogel provided by the invention is organic / inorganic composite aerogel, and through combination of rigid modified zirconium phosphate and flexible polyimide, the aerogel is endowed with excellent mechanical properties, high elasticity and high pressure resistance; the aerogel contains three flame-retardant groups of nitrogen, phosphorus and silicon, so that the heat-insulating and flame-retardant properties of the aerogel are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogel materials, and in particular to an aerogel based on bisphenol A type diether dianhydride monomer and a preparation method thereof. Background Art

[0002] Aerogel material is a new type of material with a lightweight, porous, three-dimensional network structure. It has broad application prospects in aerospace, catalysis, sensors, thermal insulation, sound insulation, solvent adsorption and other fields. In the field of flame retardant and thermal insulation, compared with traditional thermal insulation materials, aerogel materials have extremely low thermal conductivity. Its extremely low volume density and the tortuous path of the porous structure prevent gaseous and solid heat conduction, and the "infinite" void walls can minimize thermal radiation. Therefore, aerogel can be used as a fireproof and thermal insulation material in battery systems to improve the safety of lithium batteries, and can be made into flame-retardant sensors to play a role in portable devices and human-computer interaction. In addition, flame-retardant gas aerogels can also be used as coatings in the field of building insulation.

[0003] Polyimide aerogel is a special type of organic aerogel that has excellent thermal insulation and thermal stability, high temperature resistance, mechanical strength and other properties, and can withstand stress and load to a certain extent. However, during the preparation of polyimide aerogel, the strength of the polyimide precursor-polyamic acid obtained by polymerization of diamine and dianhydride as raw materials is relatively low, which is reflected in the typical gel state. It is easy to change and difficult to recover under the action of external force, and the volume shrinkage is serious; the prepared aerogel has problems such as poor surface quality, low strength, and large-size manufacturing stress concentration; it may also cause the aerogel to crack. Therefore, it is necessary to develop a new type of aerogel that can achieve enhanced flame retardant and thermal insulation effects while having flexible mechanical properties to meet long-term use requirements. Summary of the invention

[0004] In order to solve the above problems, the present invention provides an aerogel based on bisphenol A diether dianhydride monomer and a preparation method thereof. The aerogel has polyimide as a skeleton and nano zirconium phosphate material interspersed therein, which improves the toughness of the aerogel while suppressing its volume shrinkage, and has excellent flame retardant and heat insulation properties.

[0005] The first object of the present invention is to provide a method for preparing an aerogel based on bisphenol A diether dianhydride monomer, comprising the following steps:

[0006] Step 1: synthesizing a flame retardant diamine, specifically comprising:

[0007] S1: In an organic solvent 1, phosphorus oxychloride and a dihydroxy aldehyde undergo a nucleophilic substitution reaction in the presence of an acid binding agent to generate a chlorophosphate-based aldehyde, wherein the hydroxyl group in the dihydroxy aldehyde is an alcohol and / or a phenolic hydroxyl group;

[0008] S2: In organic solvent 2, the nitrogen heterocyclic diamine and the chlorophosphate aldehyde obtained in S1 undergo Schiff base reaction in the presence of an alkaline reagent to generate a chlorophosphate amine;

[0009] S3: In an organic solvent 3, dihydroxysilane and the chlorophosphorylamine obtained in S2 undergo a substitution reaction in the presence of an acid binding agent to obtain a flame retardant diamine, wherein the hydroxyl group in the dihydroxysilane is an alcohol and / or a phenolic hydroxyl group;

[0010] Step 2: In an organic solvent 4, a flame-retardant diamine and bisphenol A diether dianhydride undergo a condensation reaction to obtain a polyamic acid prepolymer;

[0011] Step 3: Add modified zirconium phosphate and a cosolvent to the polyamic acid prepolymer solution, perform ultrasonic dispersion and electromagnetic stirring successively, and seal after thorough dispersion; perform low-temperature freezing to complete the sol-gel transformation to obtain a polyamic acid salt-zirconium phosphate gel; and perform freeze-drying to obtain a polyamic acid-zirconium phosphate composite aerogel, wherein the mass of the modified zirconium phosphate is equivalent to 1wt% to 8wt% of the mass of the polyamic acid prepolymer.

[0012] Step 4: The aerogel obtained in step 3 is subjected to thermal imidization treatment in a muffle furnace to obtain a polyimide-zirconium phosphate composite aerogel.

[0013] On the basis of the above technical solution, the present invention can also be improved as follows:

[0014] Furthermore, the substitution reaction conditions in step 1 S1 are: reacting at 0° C. for 1 to 2 hours under nitrogen atmosphere and acid binding agent conditions, and then reacting at room temperature for 6 hours; the molar ratio of phosphorus oxychloride, dihydroxy aldehyde, and acid binding agent is (1.1 to 1.3):1:1;

[0015] The Schiff base reaction conditions in S2 are: stirring at 50-80° C. overnight under a nitrogen atmosphere and an alkaline reagent; the molar ratio of the chlorophosphate aldehyde, the nitrogen heterocyclic diamine and the alkaline reagent is 1:(1.2-1.5):2; since the Schiff base is generally stable at a pH value higher than 7, the alkaline reagent is used to control the system pH to 7-8;

[0016] The substitution reaction conditions in S3 are: under nitrogen atmosphere and acid binding agent conditions, stirring the reaction at 40-60° C. for 24 hours; the feeding molar ratio of chlorophosphorylamine, terminal dihydroxysilane and 4-dimethylaminopyridine is (1.1-1.3):1:1.

[0017] Furthermore, the acid binding agent in step 1 S1 and S3 is independently selected from one of trimethylamine, triethylamine, N,N-diisopropylethylamine, tetramethylammonium hydroxide, N-methylmorpholine, sodium methoxide, sodium ethoxide, potassium tert-butoxide, butyl lithium, and tert-butyl lithium; the alkaline reagent in step 1 S2 is selected from potassium carbonate or sodium bicarbonate; the organic solvents 1, 2, and 3 in step 1 are independently selected from one or more of 1,2-dichloroethane, ethyl acetate, tetrahydrofuran, and acetone.

[0018] Furthermore, the dihydroxyaldehyde in S1 is selected from one of the following structures:

[0019]

[0020] Furthermore, the nitrogen heterocyclic diamine described in S2 is pyrrole, imidazole, thiazole, furazan, pyridine, pyrimidine, pyrazine, pyridazine and their derivatives containing two primary amino substituents; the remaining substituents on the nitrogen heterocyclic ring are hydrogen atoms and / or alkyl (oxygen / sulfur / ester) groups and / or benzyl (sulfur / oxygen) groups and / or hydroxyl (alkyl) groups and / or thiol groups.

[0021] The relevant terms used in this article are further explained: the term alkyl (oxygen / thio / ester) group refers to alkyl, alkoxy, alkylthio, and alkyl ester groups with a C1-C4 carbon chain; benzyl (thio / oxygen) group refers to benzyl, benzyloxy, and benzylthio; hydroxy (alkyl) group refers to hydroxyl and terminal / side hydroxyalkyl groups with a C1-C4 carbon chain.

[0022] The present invention selects nitrogen heterocyclic diamine as the functional group of the flame-retardant diamine: the nitrogen heterocyclic can promote the carbonization of the material into a carbon layer during the combustion process, isolating oxygen and heat; it can also promote the generation of phosphate and form a protective layer on the surface of the material, further reducing the combustion speed and improving its flame retardant effect. In addition, the polarity of the N atom in the nitrogen heterocyclic can also improve the mechanical properties of the polyimide.

[0023] Furthermore, the dihydroxysilane in S3 is selected from one of the following structures:

[0024]

[0025]

[0026] Through nucleophilic substitution reaction, the hydrophobic groups silylmethyl and alkyl / benzyl in dihydroxysilane are introduced into the diamine monomer, which can help the dehydrating agent penetrate into the wet gel during the hydrogel preparation process and give the aerogel a certain hydrophobicity.

[0027] Furthermore, the specific operation of step 2 is: dissolving the flame-retardant diamine in an anhydrous organic solvent 4 under a nitrogen atmosphere, and then adding bisphenol A diether dianhydride and stirring to mix; heating to 0°C to 10°C and stirring to react for 4 to 8 hours; after completion, cooling to room temperature and standing to obtain a polyamic acid prepolymer.

[0028] The molar ratio of the flame retardant diamine to bisphenol A diether dianhydride is 1:(1.01-1.05);

[0029] The organic solvent 4 is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, N,N-diethylacetamide, N,N-diethylpropionamide, dimethyl sulfone, dimethyl sulfoxide, and N-methylpyrrolidone.

[0030] Furthermore, the mass of the modified zirconium phosphate in step 3 is equivalent to 4wt% to 8wt% of the mass of the polyamic acid prepolymer;

[0031] The cosolvent is one of triethylamine, trialkyl tertiary amine, octadecyl dimethyl tertiary amine and dodecyl dimethyl tertiary amine;

[0032] The temperature of the low-temperature freezing is -20°C, and the freezing time is 20 to 24 hours; the cold trap temperature of the vacuum freeze drying is -80°C, the vacuum degree is less than 0.1 kPa, and the drying time is 40 to 48 hours.

[0033] Furthermore, the modified zirconium phosphate described in step three is tetrakis(2-hydroxyethyl)ammonium chloride intercalated modified α-zirconium phosphate. Intercalation modification of α-zirconium phosphate with quaternary ammonium salt can improve its dispersibility and compatibility, so that the zirconium phosphate sheet can be evenly dispersed in the polyamic acid polymer solution. Because the interlayer spacing of α-zirconium phosphate is small, tetrakis(2-hydroxyethyl)ammonium chloride is difficult to directly and quickly insert between the α-zirconium phosphate layers, and a "pre-support" process of propylamine is required. The specific operation is:

[0034] α-zirconium phosphate powder and propylamine are dissolved in deionized water, first ultrasonically stirred for 10 to 20 minutes, and then mechanically stirred for 12 hours to gel the α-zirconium phosphate; then tetrakis(2-hydroxyethyl)ammonium chloride is added, and mechanically stirred at 60° C. for 24 hours; the product is centrifuged, filtered, washed, and dried to obtain modified zirconium phosphate powder.

[0035] The molar ratio of the α-zirconium phosphate, propylamine and tetrakis(2-hydroxyethyl)ammonium chloride is 1:2:(2-3); and the molar concentration of the α-zirconium phosphate is 0.2-0.4 mol / L.

[0036] α-Zirconium phosphate (Zr(HPO4)2·H2O) is a multifunctional mesoporous material with low expansion coefficient and low dielectric constant. In terms of flame retardancy, it has outstanding solid acid catalytic carbonization effect and barrier effect brought by lamellar structure. There are Lewis acid points and Bronsted acid points with catalytic activity between the layers, which can catalyze the degradation of polymer into carbon during high-temperature combustion to form a barrier; at the same time, it can also react with the acid source in the system to generate a cross-linked network structure, thereby making the expanded carbon layer more stable; the lamellar structure of zirconium phosphate itself plays a gas barrier role in the expanded carbon layer, blocking the transmission of combustible gas, oxygen and heat.

[0037] Furthermore, the thermal imidization conditions are: at a heating rate of 2 to 4°C / min, the mixture is treated at 100°C, 160°C, and 220°C for 4 hours respectively, and finally at 280°C for 1 hour.

[0038] The second object is to provide an aerogel based on bisphenol A diether dianhydride monomer, which is prepared based on the above preparation method.

[0039] The advantages of the present invention are:

[0040] The aerogel provided by the present invention is an organic / inorganic composite aerogel with polyimide as the skeleton and modified zirconium phosphate material interspersed therein. The combination of rigid modified zirconium phosphate and flexible polyimide gives the aerogel excellent mechanical properties. The strong interface effect of the cross-linked network and the introduction of siloxane provide toughness; the layered zirconium phosphate material ensures mechanical strength. In addition, the silane part contained in the polyimide molecule can react with the hydroxyl group on the surface of the modified zirconium phosphate and in the intercalation layer to form a chemical bond, thereby improving the structural stability of the material and promoting the dispersion and agglomeration of zirconium phosphate. This method does not change the performance of the polymer network itself, and the preparation conditions are mild.

[0041] The organic / inorganic composite aerogel provided by the present invention has excellent high elasticity and recoverability: at the molecular scale, the repulsive force between the hydrophobic silicon methyl molecules in the cross-linked network induces a rebound effect under high compression strain, thereby obtaining good compression and deformation resistance; the imine bond generated by the Schiff base reaction gives the aerogel dynamic mechanical characteristics including self-healing and viscoelasticity, which can effectively inhibit the volume shrinkage of the aerogel and avoid deformation or cracking of the aerogel.

[0042] The aerogel preparation method involved in the present invention involves the synthesis of flame-retardant diamine and the modification of α-zirconium phosphate. The three elements of phosphorus, nitrogen and silicon are introduced into the flame-retardant diamine molecule, which can exert the synergistic flame-retardant effect of multiple flame-retardant elements; α-zirconium phosphate has an outstanding solid acid catalytic carbonization effect and a barrier effect brought by a lamellar structure, and the modified α-zirconium phosphate can further enhance the flame-retardant and heat-insulating effect of the aerogel. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 XRD patterns of α-zirconium phosphate and modified zirconium phosphate.

[0045] Figure 2 Infrared spectra of aerogels of Example 1, Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0046] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0047] In the description provided herein, the terms "comprising," "is," "containing," "having," and "including" are used in an open-ended manner and should therefore be interpreted to mean "including but not limited to." When an article, composition of matter, or method is claimed or described as "comprising" various steps or components, the apparatus, system, or method may also "consist essentially of" or "consist of" the various steps or components, unless otherwise stated.

[0048] Unless otherwise defined, the experimental materials used in the following examples and comparative examples can be purchased from conventional biochemical reagent companies.

[0049] Preparation Example: Intercalation modification of α-zirconium phosphate The α-zirconium phosphate used is a special grade α-zirconium phosphate white powder (99.9% purity) with a particle size of 0.6 μm provided by Fujian Ruisen New Materials Co., Ltd.

[0050] 0.04 mol of α-zirconium phosphate powder and 0.08 mol of propylamine were dissolved in 100 mL of deionized water, firstly ultrasonically stirred for 20 min, and then mechanically stirred for 12 h to gel the α-zirconium phosphate; then 0.1 mol of tetrakis(2-hydroxyethyl)ammonium chloride was added, and mechanically stirred at 60° C. for 24 h; the product was centrifuged, filtered, washed, and dried to obtain modified zirconium phosphate powder.

[0051] The crystal structures of α-zirconium phosphate and modified zirconium phosphate 1 were characterized by PANalytical X Pert Pro X-ray diffractometer with a voltage of 40 kV, a current of 30 mA, a scanning range of 0.5° to 20° (2θ), and a step size of 0.02°.

[0052] Depend on Figure 1It can be seen that the XRD spectrum representing α-zirconium phosphate has a low and flat baseline, sharp peaks and no impurity peaks. The characteristic peak of α-zirconium phosphate appears at 11.87°, and the corresponding interlayer spacing is 0.763nm, indicating that it has a single crystal phase and a complete layered structure; in comparison, the XRD spectrum of the modified zirconium phosphate has changed, and its characteristic peak shifts to a low angle of 3.56°; the interlayer spacing increases to 2.54nm, and the diffraction peak at 11.87° disappears, indicating that the intercalation modification of tetra(2-hydroxyethyl)ammonium chloride is complete and has successfully entered the interlayer of α-zirconium phosphate.

[0053] Example 1

[0054] An aerogel based on bisphenol A diether dianhydride monomer, the preparation method of which is as follows:

[0055] Step 1: Synthesize flame retardant diamine. Specifically include:

[0056] S1: Mix phosphorus oxychloride dissolved in dichloromethane with a dichloromethane solution containing protocatechuic aldehyde (CAS No.: 139-85-5) and N,N-diisopropylethylamine at 0°C and nitrogen atmosphere, wherein the molar ratio of phosphorus oxychloride, protocatechuic aldehyde and N,N-diisopropylethylamine is 1.1:1:1; stir the mixture for reaction at 0°C and nitrogen atmosphere for 1 hour; then stir and react at room temperature for 6 hours. After the reaction, filter, wash the product repeatedly with 5% sodium hydroxide solution and deionized water until the organic phase is neutral; evaporate the dichloromethane solvent, dry, and obtain chlorophosphate aldehyde 1 with a yield of 83.5%.

[0057] S2: In a nitrogen atmosphere, add chlorophosphate aldehyde 1 and 6-methyl-2,4-pyrimidinediamine (CAS No.: 1791-73-7) in anhydrous 1,2-dichloroethane at a molar ratio of 1:1.2, stir and dissolve, add a slightly excess amount of potassium carbonate to maintain the pH value of the mixture solution at 7-8, and stir the mixture solution at 80°C for 12 hours; after the reaction is completed, cool the reaction mixture to room temperature, evaporate the solvent, wash with brine to remove excess amine, and then extract with ethyl acetate (150mL×2), wash the organic layer with 50ml of water, dry with sodium sulfate, and concentrate. Then, rotary evaporate the ethyl acetate under reduced pressure to obtain chlorophosphate amine 1 with a yield of 95%.

[0058] S3: Mix dichloromethane containing chlorophosphorylamine 1 and dichloromethane containing 1,4-bis(dimethylhydroxysilyl)benzene (CAS No.: 2754-32-7) and triethylamine at 0°C and nitrogen atmosphere; wherein the molar ratio of chlorophosphorylamine 1, 1,4-bis(dimethylhydroxysilyl)benzene to triethylamine is 1.2:1:1; after uniform mixing, heat to 40-60°C and stir to react for 24h; after reaction, filter, wash the filtrate with saturated brine for 3 times, concentrate and recrystallize to evaporate the dichloromethane solvent, and dry to obtain flame-retardant diamine 1; the yield is 72.1%, and its structural formula is as follows:

[0059]

[0060] Step 2: Preparation of polyamic acid prepolymer:

[0061] In a nitrogen atmosphere, the flame retardant diamine 1 is dissolved in anhydrous N,N-dimethylacetamide and stirred to dissolve, and then bisphenol A diether dianhydride is added and stirred and mixed, and the molar ratio of the flame retardant diamine to bisphenol A diether dianhydride is 1:1.05; the temperature is raised to 0°C to 10°C and stirred for 8 hours; after the temperature is lowered to room temperature and allowed to stand, a polyamic acid prepolymer 1 is obtained. The obtained polyamic acid prepolymer 1 has the following repeating units:

[0062]

[0063] Step 3: Add 4 wt% of modified zirconium phosphate 1 and trialkyl tertiary amine to the polyamic acid prepolymer 1 solution, perform ultrasonic dispersion and electromagnetic stirring successively, and seal after stirring evenly; freeze at -20°C for 24 hours to complete the sol-gel transformation to obtain polyamic acid salt-zirconium phosphate gel; and dry under vacuum drying conditions with a cold trap temperature of -80°C and a vacuum degree of less than 0.1 kPa for 48 hours to obtain polyamic acid-zirconium phosphate aerogel.

[0064] Step 4: Put the polyamic acid-zirconium phosphate aerogel into a muffle furnace for thermal imidization treatment: at a heating rate of 3°C / min, treat at 100°C, 160°C, and 220°C for 4 hours respectively, and finally keep the temperature at 280°C for 1 hour to obtain polyimide-zirconium phosphate aerogel.

[0065] Example 2

[0066] An aerogel based on bisphenol A diether dianhydride monomer, the preparation method is the same as that of Example 1, except that in step 1, the dihydroxy aldehyde used in S1 is 2,3-dihydroxy-2H-pyran-2-carboxaldehyde (CAS: 146664-39-3); the nitrogen heterocyclic diamine used in S2 is 1-methyl-1H-pyrrole-2,5-diamine (CAS No. 862200-46-2); the dihydroxy silane used in S3 is 3-[[(tert-butyl) silyl] oxy]-5-hydroxy-benzyl alcohol (CAS: 641571-45-1), and the solvent used is ethyl acetate. The structural formula of the flame-retardant diamine obtained in step 1 (yield 75.3%) is as follows:

[0067]

[0068] The polyamic acid prepolymer obtained in step 2 has the following repeating units:

[0069]

[0070] Example 3

[0071] An aerogel based on bisphenol A diether dianhydride monomer, the preparation method is the same as that of Example 1, except that in step 1, the dihydroxy aldehyde used in S1 is 2,3-dihydroxy-2H-pyran-2-carboxaldehyde (CAS: 146664-39-3); the nitrogen heterocyclic diamine used in S2 is 4,5-diaminofurazan (CAS No. 17220-38-1); the dihydroxy silane used in S3 is 3-[[(tert-butyl) silyl] oxy]-5-hydroxy-benzyl alcohol (CAS: 641571-45-1), and the solvent used is tetrahydrofuran. The structural formula of the flame-retardant diamine obtained in step 1 (yield 71.3%) is as follows:

[0072]

[0073] The polyamic acid prepolymer obtained in step 2 has the following repeating units:

[0074]

[0075] Embodiment 4 to Embodiment 6

[0076] An aerogel based on bisphenol A diether dianhydride monomer, the preparation method is different from that of Example 1 in that the mass of the modified zirconium phosphate added in step 3 is different. Specifically, 2wt%, 6wt%, and 8wt% of the modified zirconium phosphate equivalent to the mass of the polyamic acid prepolymer are added to the polyamic acid prepolymer solution.

[0077] Comparative Example 1

[0078] An aerogel based on bisphenol A type diether dianhydride monomer, the preparation method is different from that of Example 1 in that step one is omitted, that is, in step two, 6-methyl-2,4-pyrimidinediamine is directly used as a diamine monomer to polymerize with the bisphenol A type diether dianhydride monomer, and the other conditions are the same as those of Example 1.

[0079] The polyamic acid prepolymer obtained in step 2 has the following repeating units:

[0080]

[0081] Comparative Example 2

[0082] An aerogel based on bisphenol A diether dianhydride monomer, the preparation method is different from that of Example 1 in that modified zirconium phosphate is not added in step 3; the other conditions are the same as those of Example 1. 1. Chemical composition test:

[0083] The chemical composition of the aerogels obtained in Test Example 1, Comparative Example 1 and Comparative Example 2 was analyzed by using a Bruker VERTEX 80 Fourier transform infrared spectrometer. The resolution was 2 cm -1 , scan times 32 times, test results see Figure 2 .

[0084] Depend on Figure 2 , the three samples are at 2800~3000cm -1 The typical absorption of polyimide includes: -1 、1070cm -1 The peaks at 1780 cm-1 are the asymmetric and symmetric stretching peaks of the ether (COC) bond; -1 With 1725cm -1 The peaks at 725cm-1 are the asymmetric and symmetric stretching vibration characteristic peaks of the C=O bond of the imide ring; and -1 The absorption peak at is attributed to the bending vibration of the C=O bond.

[0085] Example 1 and Comparative Example 1 at 3000-3500cm -1 The broad absorption in the range is caused by the amino groups in the polyimide, the P-OH groups in the modified zirconium phosphate, and the -OH groups on the intercalated tetra(2-hydroxyethyl)ammonium chloride molecules; this indicates that the introduction of modified zirconium phosphate enhances the hydrogen bonding effect. -1 、1380cm -1 The stretching vibrations of POC bond and P=O bond are respectively contained in Comparative Example 1, and there is no absorption at these locations. -1The strong absorption peak in the range is attributed to the stretching vibration of the POP bond. In Comparative Example 2, since no modified zirconium phosphate is added, the peak intensity here is significantly weakened.

[0086] Example 1 at 1630cm -1 The absorption peak of the C=N bond stretching at 836 cm is stronger than that of Comparative Example 1. This is because the diamine monomer used in Comparative Example 1 has not been flame-retardantly modified, does not contain an imine bond formed by a Schiff base reaction, and only has the absorption of the C=N bond of the pyrimidine ring; at the same time, it does not contain the absorption peak of Example 1 and Comparative Example 2 at 836 cm -1 、807cm -1 The stretching vibration absorption peaks belong to the Si-C bond and Si-O bond respectively.

[0087] 2. Performance testing

[0088] The aerogels prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were tested:

[0089] Shrinkage rate: The initial size of the aerogel before complete drying and the final size after drying (including length, width, and height) were recorded and calculated according to the following formula: Shrinkage rate = (initial size - final size) / initial size × 100%.

[0090] Compression strength: tested using an instron universal testing machine at a compression rate of 2 mm / min at room temperature; Tensile strength: tested using the GB2567-2008 method at room temperature.

[0091] Thermal conductivity: According to GBT32064-2015 test standard, tested by thermal conductivity meter.

[0092] Compressive stress: The test was conducted by applying a 1000 g weight on the aerogel at a test temperature of 25 °C.

[0093] Glass transition temperature (T g ): Tested by TAQ20 differential scanning calorimeter (DSC). Before the test, the sample was dried at 120℃ for 4h, 6-8mg sample was weighed, and the test was carried out in a nitrogen atmosphere with a nitrogen flow rate of 20mL / min; the first heating rate was 20℃ / min, the heating temperature range was 40-400℃; kept at 400℃ for 2min; then the temperature was rapidly reduced, the cooling temperature range was 40-400℃; kept at 40℃ for 2min; then the second heating was carried out, the heating rate was 20℃ / min, and the heating temperature range was 40-400℃.

[0094] 5% thermal weight loss temperature (T 5%): Tested using TAQ500 thermogravimetric analyzer. The nitrogen flow rate was 50 mL / min, the heating rate was 10 °C / min, and the test range was room temperature to 800 °C. The aerogel sample was dried in an oven at 120 °C for 6 hours before testing to eliminate the interference of the solvent, and then accurately weighed 2 to 3 mg for testing.

[0095] Limiting oxygen index (LOI): The test was conducted using a JE-5 fully automatic oxygen index tester (Nanjing Jionglei Instrument Equipment Co., Ltd.) in accordance with GB / T 5454-1997 “Oxygen Index Method for Textile Combustion Performance Test”. The sample size was 110 mm × 6 mm × 2 mm.

[0096] The results of the above tests are listed in Table 1 below.

[0097] Table 1

[0098]

[0099] From Table 1, compared with Comparative Example 1, the flame retardant modification of the diamine monomer increases the cross-linking network of the polyimide and the porosity; the glass transition temperature and thermal weight loss temperature of the aerogel are also significantly improved, and the barrier effect of various flame retardant groups and modified zirconium phosphate gives the aerogel further enhanced heat resistance and flame retardant properties; compared with Comparative Example 2, the doping of modified zirconium phosphate in the PI matrix greatly improves the thermal and mechanical properties of the composite aerogel: the dispersed modified zirconium phosphate nanosheets can produce rich interface interactions with the PI matrix, promote the transfer of external stress, heat, etc. from the PI matrix to the surface of the modified zirconium phosphate nanosheets, and significantly enhance the thermal and mechanical properties of the composite aerogel.

[0100] The polyimide / zirconium phosphate composite hydrogel obtained by the present invention performs well in thermal conductivity and limiting oxygen index; at the same time, the compression strength and tensile strength results show that the aerogel has good compression and deformation resistance and excellent comprehensive performance.

[0101] It should be noted that the above embodiments and comparative examples are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing an aerogel based on bisphenol A diether dianhydride monomer, characterized in that: The following steps are involved: Step 1: synthesizing flame retardant diamine, specifically comprising: S1: In an organic solvent 1, phosphorus oxychloride and a dihydroxy aldehyde undergo a nucleophilic substitution reaction in the presence of an acid binding agent to generate a chlorophosphate-based aldehyde; the hydroxyl group in the dihydroxy aldehyde is an alcohol and / or a phenolic hydroxyl group; S2: In organic solvent 2, the nitrogen heterocyclic diamine and the chlorophosphate aldehyde obtained in S1 undergo Schiff base reaction in the presence of an alkaline reagent to generate a chlorophosphate amine; S3: In an organic solvent 3, dihydroxysilane and the chlorophosphorylamine obtained in S2 undergo a substitution reaction in the presence of an acid binding agent to obtain a flame-retardant diamine; the hydroxyl group in the dihydroxysilane is an alcohol and / or a phenolic hydroxyl group; Step 2: In an organic solvent 4, a flame-retardant diamine and bisphenol A diether dianhydride undergo a condensation reaction to obtain a polyamic acid prepolymer; Step 3, adding modified zirconium phosphate and a cosolvent to the polyamic acid prepolymer solution, performing ultrasonic dispersion and electromagnetic stirring successively, and sealing after thorough and uniform dispersion; Low temperature freezing to complete the sol-gel transformation to obtain a polyamic acid salt-zirconium phosphate gel; then freeze drying to obtain a polyamic acid-zirconium phosphate composite aerogel; the mass of the modified zirconium phosphate is equivalent to 1wt% to 8wt% of the mass of the polyamic acid prepolymer; Step 4: The aerogel obtained in step 3 is subjected to thermal imidization treatment in a muffle furnace to obtain a polyimide-zirconium phosphate composite aerogel.

2. The method for preparing aerogel based on bisphenol A diether dianhydride monomer according to claim 1, characterized in that: Step 1 S1: The substitution reaction conditions are: reacting at 0°C for 1-2h under nitrogen atmosphere and acid binding agent, and then reacting at room temperature for 6h; the molar ratio of phosphorus oxychloride, dihydroxy aldehyde and acid binding agent is (1.1-1.3):1:1; The Schiff base reaction conditions in S2 are: stirring at 50-80° C. overnight under a nitrogen atmosphere and an alkaline reagent; the molar ratio of the chlorophosphate aldehyde, the nitrogen heterocyclic diamine and the alkaline reagent is 1:(1.2-1.5):2; The substitution reaction conditions in S3 are: under nitrogen atmosphere and acid binding agent conditions, stirring the reaction at 40-60° C. for 24 hours; the feeding molar ratio of chlorophosphorylamine, terminal dihydroxysilane and 4-dimethylaminopyridine is (1.1-1.3):1:

1.

3. The method for preparing aerogel based on bisphenol A diether dianhydride monomer according to claim 1, characterized in that: The acid binding agent in step 1 S1 and S3 is independently selected from one of trimethylamine, triethylamine, N,N-diisopropylethylamine, tetramethylammonium hydroxide, N-methylmorpholine, sodium methoxide, sodium ethoxide, potassium tert-butoxide, butyl lithium, and tert-butyl lithium; the alkaline reagent in step 1 S2 is selected from potassium carbonate or sodium bicarbonate; the organic solvents 1, 2, and 3 in step 1 are independently selected from one or more of 1,2-dichloroethane, ethyl acetate, tetrahydrofuran, and acetone.

4. The method for preparing aerogel based on bisphenol A diether dianhydride monomer according to claim 1, characterized in that: The dihydroxyaldehyde in S1 is selected from one of the following structures:

5. The method for preparing aerogel based on bisphenol A diether dianhydride monomer according to claim 1, characterized in that: The nitrogen heterocyclic diamine described in S2 is pyrrole, imidazole, thiazole, oxazole, pyridine, pyrimidine, pyrazine, pyridazine and their derivatives containing two primary amino substituents; the remaining substituents on the nitrogen heterocyclic ring are hydrogen atoms and / or alkyl (oxygen / sulfur / ester) groups and / or benzyl (sulfur / oxygen) groups and / or hydroxyl (alkyl) groups and / or thiol groups.

6. The method for preparing aerogel based on bisphenol A diether dianhydride monomer according to claim 1, characterized in that: The dihydroxysilane in S3 is selected from one of the following structures:

7. The method for preparing aerogel based on bisphenol A diether dianhydride monomer according to claim 1, characterized in that: The reaction conditions of step 2 are: dissolving the flame-retardant diamine in an anhydrous organic solvent 4 under a nitrogen atmosphere, then adding bisphenol A diether dianhydride and stirring and mixing; heating to 0°C to 10°C and stirring and reacting for 4h to 8h; after the reaction is completed, cooling to room temperature and standing to obtain a polyamic acid prepolymer; The molar ratio of the flame retardant diamine to bisphenol A diether dianhydride is 1:(1.01-1.05); The organic solvent 4 is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, N,N-diethylacetamide, N,N-diethylpropionamide, dimethyl sulfone, dimethyl sulfoxide, and N-methylpyrrolidone.

8. The method for preparing aerogel based on bisphenol A diether dianhydride monomer according to claim 1, characterized in that: The mass of the modified zirconium phosphate in step 3 is equivalent to 4% to 8% of the mass of the polyamic acid prepolymer; The cosolvent is one of triethylamine, trialkyl tertiary amine, octadecyl dimethyl tertiary amine and dodecyl dimethyl tertiary amine; The temperature of the low-temperature freezing is -20°C, and the freezing time is 20 to 24 hours; the cold trap temperature of the vacuum freeze drying is -80°C, the vacuum degree is less than 0.1 kPa, and the drying time is 40 to 48 hours.

9. The method for preparing aerogel based on bisphenol A diether dianhydride monomer according to claim 1, characterized in that: The modified zirconium phosphate described in step 3 is intercalation modified α-zirconium phosphate, and the specific modification operation is: dissolving α-zirconium phosphate powder and propylamine in deionized water, first ultrasonically stirring for 10 to 20 minutes, and then mechanically stirring for 12 hours to gel the α-zirconium phosphate; then adding tetrakis(2-hydroxyethyl)ammonium chloride, and mechanically stirring at 60° C. for 24 hours; the product is centrifuged, filtered, washed, and dried to obtain modified zirconium phosphate powder; The molar ratio of the α-zirconium phosphate, propylamine and tetrakis(2-hydroxyethyl)ammonium chloride is 1:2:(2-3); and the molar concentration of the α-zirconium phosphate is 0.2-0.4 mol / L.

10. An aerogel, characterized in that: The aerogel is prepared by the preparation method based on bisphenol A diether dianhydride monomer according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Nitrogen-phosphorus compound intercalation modified zirconium phosphate with flame-retardation effects and preparation method

    CN109438759A

  • Cardanol-based halogen-free flame-retardant toughening agent as well as preparation method and application thereof

    CN111205316A

  • Preparation method of biomass boron nitride nanosheet modified polyimide aerogel

    CN114395163A

  • Phenylboronic acid grafted modified zirconium phosphate-based flame retardant and preparation method therefor

    WO2022160673A1